MAKNA KIASAN DALAM RANGKAIAN TRADISI MANGGODOK NAGARI KUBANG NAN DUO KECAMATAN PAYUANG SEKAKI KABUPATEN SOLOK (KAJIAN SEMANTIK) - Ika Kamila Sari; Zona Rida Rahayu; Rini Wirasty B. (Program Studi Pendidikan Bahasa Indonesia, , Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mahaputra Muhammad Yamin, 2023)
The background of this research is that the people of Nagari Kubang Nan Duo, Payuang Sekaki District, Solok Regency, do not understand figurative eating itself. The manggodok tradition is not something that is done without any meaning behind it. A group of people carry out a custom or tradition without understanding the meaning of the custom itself which results in the community not understanding the series of customs themselves. Therefore, it is feared that there will be ignorance in the regional culture so that the cultural values ​​in it will fade and disappear slowly. The purpose of this research is to describe the figurative meaning of the manggodok tradition in Nagari Kubang Nan Duo, Payuang Sekaki District, Solok Regency (Semantic Review). This type of research is qualitative research using a descriptive approach. The object of this research is the Manggodok tradition in Nagari Kubang Nan Duo, Payuang Sekaki District, Solok Regency (Semantic Review). The steps for collecting data in this study are as follows: 1) Researchers carry out field observations by coming directly to the house where the manggodok tradition is carried out. 2) Doing documentation or taking photos in the manggodok tradition in Nagari Kubang Nan duo, Payuang Sekaki District, Solok Regency. 3) interviewing and recording informants' speeches as well as asking questions about the manggodok tradition. 4) Record the results of the interviews that have been interviewed. The findings of the semantic review research are idioms, expressions, and proverbs. Based on the data obtained in the research, the figurative meaning in the manggodok nagari tradition of Kubang Nan Duo, Payuang Sekaki District, Solok Regency (Semantic Study) contains a total of 46 data, 20 idiom data, 17 expression data, and 9 proverb data. These semiotic studies cannot be separated from one another. It is hoped that the community will be able to preserve and apply figurative meanings in the series of manggodok nagari Kubang Nan Duo traditions, Payuang Sekaki District, Solok Regency.